The Happy Warrior: Winston Churchill and the Representation of War, 1895–1901 - Antoine Capet (Cahiers Victoriens et Edouardiens)
That Churchill found the glory and dangers of war attractive is in no doubt. Most people today only remember his massive role in the British war effort during the Second World War, but in fact he was an active participant in more distant conflicts—as frontline observer or combatant—as early as 1895, when he used his parents’ connections in high places to obtain permission to go to Cuba, where a war of independence was taking place. The British Empire of course provided ample scope for military adventure, and once again young Churchill had all possible strings pulled for him in order to allow him to join the peace-keeping (in the sense of Pax Britannica) operations on the North-West frontier of India, in the Sudan (where he famously participated in the last cavalry charge in British history) and finally in South Africa, where his daring escape from his Boer prison in 1900 made him a world-wide celebrity. In all this, Churchill’s sense for self-publicity, which necessitated a glorification of war (no danger—no merit—no glory), seems to have projected a very misleading image of war as it really was at the turn of the century—his later description of these wars as “cruel and magnificent”, as opposed to the “cruel and squalid” war of 1914–1918 appears to belong with the celebrated “Churchill rhetoric”, in tune with the jingoistic atmosphere of the times, rather than historical fact.